Effect of adipose tissue deposition on insulin resistance in middle‐aged and elderly women: Based on QCT and MRI mDIXON‐Quant - Ying Liu; Lei Gao; Mengfei Wu; Boyang Yang; Dongxue Ren; Zekun Zhang; Wei Zhang; Yan Wang (Journal of Diabetes Investigation)
Objective To explore the relationship between adipose tissue deposition and triglyceride‐glucose (TyG) index, an indicator clinically used to assess insulin resistance (IR), in middle‐aged and elderly women using quantitative computed tomography (QCT) and MRI mDIXON‐Quant sequence. Methods All participants underwent quantitative computed tomography (QCT) and MRI mDIXON‐Quant examination and calculated the TyG index based on the fasting blood glucose and triacylglycerol. Bounded by the median TyG index, all participants were divided into low TyG group and high TyG group. Visceral fat mass (VFM) and subcutaneous fat mass (SFM) were measured on QCT images. Hepatic proton density fat fraction (H‐PDFF), pancreatic proton density fat fraction (P‐PDFF), and lumbar bone marrow fat fraction (L‐BMFF) were measured on MRI mDIXON‐Quant images. Results Adjusting for age and body mass index (BMI), TyG was moderately positively correlated with H‐PDFF, and r/P was 0.416/<0.001, TyG index was weakly positively correlated with VFM and P‐PDFF, and r/P were 0.385/<0.001 and 0.221/0.030. There was a difference of VFM, H‐PDFF, and P‐PDFF between low TyG group and high TyG group (P < 0.05). Adjusting for age and BMI, VFM, and H‐PDFF were the risk factors of high TyG, and H‐PDFF was the independent risk factor of high TyG. Conclusions VFM and H‐PDFF were the risk factors of IR, and H‐PDFF was the independent risk factor. Early identification and active treatment of adipose tissue deposition, especially hepatic fat deposition, may reserve and delay the progression of IR and even metabolic syndrome.